The feasibility of a social media-based foot self-management education and support program for adults with diabetes: A partially randomized preference trial - Helen Ngozichukwuka Obilor; Olena Veryha; Tom Weisz; Mariam Botros; Rosemary Wilson; Joan Tranmer; Kevin Woo (Elsevier, 2024)
Aim: To assess the feasibility of Diabetic Foot Care Group (DFCG), a social media-based self-management education and support intervention, for people with diabetes (PWD) empowerment in diabetes-related foot ulceration prevention. Methods: A partially randomized preference trial was conducted among 32 PWD. DFCG was implemented through Facebook. Participants in the intervention group joined the DFCG in addition to their usual care, while the control group received usual care. Data were collected online using questionnaires on participants' DFCG acceptance, engagement and preliminary efficacy on nine diabetes foot care-related outcomes at baseline, one, and three months post-intervention. Results: The participants' study intervention acceptability and engagement rates were 84.2% and 55.2%, respectively. DFCG efficacy rate compared to usual care was 88.9% to 22.2%. Three diabetes foot care-related outcomes increased significantly in the intervention group three-month post-intervention: foot self-care adherence (p = 0.001, ηp2 = 0.35), preventive foot self-care practice (p = 0.002, ηp2 = 0.33), and physical health status (p < 0.02, ηp2 = 0.23). Conclusion: DFCG is feasible and could effectively improve diabetes foot care-related outcomes. Innovation: Social media is an innovative approach healthcare professionals could utilize to virtually support PWD in ongoing learning and engagement in optimal foot self-care activities. Trial registration: ClinicalTrials.gov, Identifier: NCT04395521